A "Rule-of-Five" Framework for Models and Modeling to Unify Mathematicians and Biologists and Improve Student Learning. Issue 8 (14th September 2019) - Diaz Eaton, C.; Highlander, H. C.; Dahlquist, K. D.; Ledder, G.; LaMar, M. D.; Schugart, R.C.
Abstract: Despite widespread calls for the incorporation of mathematical modeling into the undergraduate biology curriculum, there is lack of a common understanding around the definition of modeling, which inhibits progress. In this paper, we extend the "Rule-of-Four, " initially used in calculus reform efforts, to a "Rule-of-Five" framework for models and modeling that is inclusive of varying disciplinary definitions of each. This unifying framework allows us to both build on strengths that each discipline and its students bring, but also identify gaps in modeling activities practiced by each discipline. We also discuss benefits to student learning and interdisciplinary collaboration.